2018
DOI: 10.1111/eth.12718
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses of male ruffed grouse (Bonasa umbellus, L.) to playbacks of drumming displays

Abstract: Birds use a variety of sounds in their courtship displays, but the majority of behavioural studies have focused on vocalizations. In contrast, little is known about how non‐vocal sounds, or sonations, are used, even though many avian species produce them. The ruffed grouse (Bonasa umbellus) is a useful species to examine non‐vocal sounds because they lack vocal components in their courtship and rely on a non‐vocal sound to attract mates and defend their territory. Their courtship display, known as “drumming,” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Peahens also perform a tail-rattling display at 25–29 Hz in a variety of contexts [20], suggesting that feather vibrations might serve other communicative functions as well. Three studies have found that birds respond behaviorally to playbacks of low frequency sound generated by social displays: peafowl detect the infrasound (< 20 Hz) component of train-rattling and wing-shaking recordings [19]; male houbara bustards ( Chlamydotis undulata undulata ) respond to low frequency (40–54 Hz) boom vocalizations [22]; and male ruffed grouse ( Bonasa umbellus ) respond to 45 ± 6 Hz wing beating “drumming” displays [23]. Several other studies have also measured the behavioral response of birds to amplitude-modulated low repetition rate broad-band pulses, which are similar to the mechanical sounds associated with peacock train-rattling; the results of these studies showed that birds from three different families can detect such sounds with repetition rates < 40 Hz [2426].…”
Section: Introductionmentioning
confidence: 99%
“…Peahens also perform a tail-rattling display at 25–29 Hz in a variety of contexts [20], suggesting that feather vibrations might serve other communicative functions as well. Three studies have found that birds respond behaviorally to playbacks of low frequency sound generated by social displays: peafowl detect the infrasound (< 20 Hz) component of train-rattling and wing-shaking recordings [19]; male houbara bustards ( Chlamydotis undulata undulata ) respond to low frequency (40–54 Hz) boom vocalizations [22]; and male ruffed grouse ( Bonasa umbellus ) respond to 45 ± 6 Hz wing beating “drumming” displays [23]. Several other studies have also measured the behavioral response of birds to amplitude-modulated low repetition rate broad-band pulses, which are similar to the mechanical sounds associated with peacock train-rattling; the results of these studies showed that birds from three different families can detect such sounds with repetition rates < 40 Hz [2426].…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of suggestions that sonations and vocalizations trade off. Ruffed Grouse defend their territory with a loud wing drumming (18), and are said to have a nearly non-existent syrinx. Smithornis broadbills likewise defend territories with wing sounds (3), and reportedly have few vocalizations and a puny syrinx (19).…”
Section: How Do Sonations Coevolve With Vocalizations?mentioning
confidence: 99%
“…This represents most studied systems, but sounds of terrestrial vertebrates are not only produced in the larynx or syrinx. Several avian species are known to produce non-syrinx sounds, which can be produced by instrumental feathers (Murray, Zeil & Magrath, 2017), beak drumming (Budka et al, 2018;Dodenhoff, Stark & Johnson, 2001), wings beating (Garcia et al, 2012;O'Neil, Charrier & Iwaniuk, 2018), the rattling of mandibles (Eda-Fujiwara et al, 2004), step dances (Ota, Gahr & Soma, 2017) or else, by using tools (Heinsohn et al, 2017).…”
Section: Introductionmentioning
confidence: 99%